Information technology investments and supply chain governance - Dolci,Pietro Cunha (2014)
The aim of this research is to propose a model that relates information technology (IT) investments, supply chain governance (SCG) and performance together. For this purpose, a pilot study involving both a qualitative and a quantitative stage was conducted. The qualitative analysis, consisting of an extensive literature review and two case studies conducted in six major, globally-relevant Brazilian companies, led to the development of an initial model. This model was refined during the quantitative stage that involved 38 executives from large national companies. IT was found to be one of the main drivers of SCG influencing companies' supply chain performance. The final model consists of 5 constructs and 26 elements. Regarding the SCG constructs: (a) a new element 'formal contracts', emerged in the 'contractual SCG' construct; (b) the element 'cooperation' was not confirmed in the 'relational SCG' construct; (c) the element 'transparency' was considered an important element in the 'transactional SCG' construct. Five new elements emerged in the 'IT investment' construct. Market aspects were highlighted as being relevant in the 'supply chain performance' construct. Thus, the model includes elements that can be analyzed in order to shed light on how IT investments influence SCG and supply chain performance.